Use of Immunostimulants in Shrimp Farming—A Bioeconomic Perspective - Héctor Rodrigo Nolasco-Alzaga; Elizabeth Monreal-Escalante; Mariel Gullian-Klanian; Juan Antonio de Anda-Montañez; Antonio Luna-González; Fernando Aranceta; Marcelo E. Araneda-Padilla; Carlos Angulo (Animals)
Aquaculture is the fastest-growing food industry worldwide because it allows faster intensive production in a limited space and short time. However, the trade-off of this production scheme has led to infectious disease outbreaks that harm food production with economic impacts. Immunostimulants have entered the industry to fight against diseases by enhancing the immune system and conferring better protection against pathogens. In this regard, dietary immunostimulants have been tested at the farm level, such as carbohydrates and proteins known to enhance immunity and improve survival rates under experimental conditions. Despite the success of immunostimulant inclusion in experimental aquaculture, economic evaluation is an innovative avenue to be integrated when a novel immunostimulant is developed. The bioeconomic analysis permits the accurate demonstration of advantages or disadvantages regarding survival and yield performance upon immunostimulant application through mathematical and statistical estimates. An integrative bioeconomic model for testing a novel immunostimulant should contemplate technological, biological, and economic submodels at least; thus, financial variables, such as revenue, costs, and profitability, should also be considered for proper decision-making. Therefore, this perspective briefly describes the most relevant immunostimulants used in shrimp farms and offers bioeconomic elements that should be considered for affordable immunostimulant development and inclusion in shrimp aquaculture.